Influence of weather variables on physical activity assessed by accelerometry across age and gender groups - Bento, Teresa (2015)
The purpose of this research was to study the effects of weather on physical activity and compliance to minimum physical activity recommendations. Participants included 257 women and 178 men. Time spent in physical activity, average daily steps, and weather variables were gathered and analysed to explore the influence of weather on PA and compliance with the PA recommendations. In result, environmental factors may have a weak influence in an individual will to engage in PA, and individuals highly committed to an active lifestyle (based on the number of steps taken per day) did not seem to be influenced by any of the weather variables. To conclude, considering the known barriers to an active lifestyle, this information is markedly important since engaging in physical activity on a day-to-day basis may be of extreme relevance to the maintenance of a healthy status, especially in the elderly.